Stability and Control of Conventional and Unconventional Aerospace Vehicle Configurations A Generic Approach from Subsonic to Hypersonic Speeds - Chudoba, Bernd (Springer Aerospace Technology, 2019)
This book introduces a stability and control methodology named AeroMech, capable of sizing the primary control effectors of fixed wing subsonic to hypersonic designs of conventional and unconventional configuration layout. Control power demands are harmonized with static-, dynamic-, and maneuver stability requirements, while taking the six-degree-of-freedom trim state into account. The stability and control analysis solves the static- and dynamic equations of motion combined with non-linear vortex lattice aerodynamics for analysis. The true complexity of addressing subsonic to hypersonic vehicle stability and control during the conceptual design phase is hidden in the objective to develop a generic (vehicle configuration independent) methodology concept. The inclusion of geometrically asymmetric aircraft layouts, in addition to the reasonably well-known symmetric aircraft types, contributes significantly to the overall technical complexity and level of abstraction. The first three chapters describe the preparatory work invested along with the research strategy devised, thereby placing strong emphasis on systematic and thorough knowledge utilization. The engineering-scientific method itself is derived throughout the second half of the book. This book offers a unique aerospace vehicle configuration independent (generic) methodology and mathematical algorithm. The approach satisfies the initial technical quest: How to develop a 'configuration stability & control' methodology module for an advanced multi-disciplinary aerospace vehicle design synthesis environment that permits consistent aerospace vehicle design evaluations?